Observer-based backstepping boundary control for a flexible riser system. (October 2018) - Guo, Fang; Liu, Yu; Wu, Yilin; Luo, Fei
Highlights: The flexible riser system is regarded as a distributed parameter system. A boundary disturbance observer is to compensate for boundary disturbance. An infinite dimensional disturbance observer is to handle distributed disturbance. The control approach is to achieve disturbance rejection and vibration abatement. The well-posedness of the closed-loop riser system is demonstrated. Abstract: In order to achieve the disturbance rejection and vibration abatement of a flexible marine riser system, this article discusses the design of disturbance observers and controller. The riser system subjected to external disturbances is a distributed parameter system in essence and represented by infinite-dimensional equation coupled with finite-dimensional equations. In addition to designing a basic boundary disturbance observer to deal with the time-varying boundary disturbance in this paper, an innovative infinite dimensional disturbance observer is also designed to compensate for the spatially distributed disturbance. Applying these two observers as feedforward compensators, an observer-based boundary controller is formulated by means of combining backstepping technique with boundary control method. Moreover, the well-posedness of the closed-loop riser system is discussed, and simulations are presented to display the effectiveness of formulated control approach.